AEG-1/MTDH: A central regulator of tumor progression, metabolic adaptation, and therapeutic resistance in gliomas - Suleiman Ibrahim Mohammad; Asokan Vasudevan; Mutaz Jamal Al-khreisat; Safa H. Radhie; Zukhra Yakhshieva; Ibrokhim Sapaev; Mirza R. Baig; Navin Kumar Tailor; Divya Singhal; Amr Ali Mohamed Abdelgawwad El-Sehrawy (Tissue and Cell, 2027)

System dynamics modelling of India’s net zero transition - Ramya Natarajan; Aparna Sundaresan; Kaveri Ashok; Anasuya Gangopadhyay; Divya Davis; Krithika Ravishankar; Sweta Bhushan; Sarah Khan; Kunal Jagdale; Upasna Ranjan; Chandrakiran L; Indu K Murthy; et al. (Energy and Climate Change, 2026)

Scale-up of rhamnolipid biosynthesis via agro-waste valorization: Techno-economic assessment with cradle-to-gate life cycle analysis - Sourab Paul; Jayato Nayak; Divya Khare; Md Monjurul Islam; Ramesh Kumar; Byong-Hun Jeon (Biomass and Bioenergy, 2026)

Gamete co-incubation duration modulates blastocyst developmental competence in buffalo through regulation of growth factors, steroidogenesis and oxidative stress pathways - Garbhit Sharma; Anand Kumar Pandey; Hitesh Jangra; Sandeep Kumar; Pradeep Saini; Rajesh Kumar; Divya Choudhary (Molecular Biology Reports, 2026)

MGMT promoter methylation across glioma subtypes: biological relevance, treatment response, and survival outcomes - Usamah Sayed; Rano Alieva; Malathi Hanumanthayya; Divya Singhal; Rajashree Panigrahi; Navin Kumar Tailor; Tulkin Buzrukov; Sirojiddin Norkulov (Molecular Biology Reports, 2026)

TLR ligands as immunomodulators: mechanistic insights and therapeutic potential in infectious and inflammatory diseases - Divya Verma; Sarthak Dhar; Takhellambam Malemnganba; Sanyukta Sharma; Sramona Kar; Vijay Kumar Prajapati (Molecular Biology Reports, 2026)

Deciphering genetic diversity and selection footprints in Rathi cattle through ddRAD-based genome-wide analysis - Nishu Bharia; Anal Bose; Sonali Sonejita Nayak; Divya Rajawat; Vijay Kumar; Triveni Dutt; Manjit Panigrahi (Mammalian Genome, 2026)

Genome-wide characterization of genetic diversity and breed discrimination markers in Tharparkar cattle - Anal Bose; Nishu Bharia; Sonali Sonejita Nayak; Divya Rajawat; Pallavi Hembrom; Vijay Kumar; Sita Ram Gupta; Manjit Panigrahi (Mammalian Genome, 2026)

Comparative in vitro Evaluation of Ion-Exchange Resin–Based Taste-Masked Orodispersible Tablets of Ambroxol Hydrochloride - Divya Avasthi; Sharad Pawar; Sudheer Kumar; Shubham Sharma (Journal of Pharmaceutical Innovation, 2026)

Integrated genome-wide association study (GWAS) and metabolomics identify genetic and metabolic drivers of stripe rust resistance in wheat from the Western Himalayas - Farkhandah Jan; M. Parthiban; Sofora Jan; Anjan Kumar Pradhan; Sundeep Kumar; Safoora Shafi; Mahpara Bashir; Divya Sharma; Naeela Qureshi; Manish Kumar Vishwakarma; Sarabjit Kaur; Jaspal Kaur; et al. (Functional & Integrative Genomics, 2026)

Sustainable tetracycline removal using waste derived CaO modified biochar: RSM optimization, machine learning prediction and cost analysis - Divya Dhillayan; Santosh Bhukal; Sanjay Kumar; Suresh Ghotekar; Navish Kataria (Biomass and Bioenergy, 2026)

A comprehensive review of IoT-enabled microgrids: architectures, challenges, and future prospects to achieve sustainability - Divya Chauhan; Khushi Shukla; Dhruvi Desai; Tirth Borasaniya; Raj Jadav; Alok Kumar Singh; Bablu Kumar Singh; Ajay Kumar Vyas (Next Research, 2026)

Evaluating ERA5-Land air temperature and dew point biases in built-up environments in the UK - Junjie Yu; Wenyuan Li; Lingcheng Li; Divya Kumar; Hongyu Sun; David O. Topping; Guoqiang Tang; Zhonghua Zheng (Urban Climate, 2026)

Green-synthesized iron oxide nanoparticles enhance the synergistic effects of Alcaligenes faecalis CJSKII3 on growth promotion and antioxidant properties in okra - Divya Bhagat; Mandeep Kaur; Sakshi Chopra; Praveen Guleria; Vineet Kumar (Rhizosphere, 2026)

Comparative structural, evolutionary, and functional insights into rice γ-glutamyl cyclotransferases reveal differential stability and stress-responsive expression - Divya Chaudhary; Himanshi Aggarwal; Aman Choudhary; Nischal Pradhan; Bhoopander Giri; Vaibhav Mishra; Navaneet Chaturvedi; Prashant Kumar Singh; Laurent Dufossé; Naveen Chandra Joshi (Plant Gene, 2026)

Assessment of design challenges and viability of wireless electric vehicle charging stations in residential setup to empower sustainable e-mobility: A comprehensive review - Anubhav Kumar Pandey; Nandini K․ K․; Suvetha P S; Abhinandan S Marashiddannavar; Divya Jaganath; Chandana Govindanayak; Anand Reddy (Next Research, 2026)

Uncertainty-aware semi-supervised framework with supervised contrastive learning for sugarcane leaf disease detection - Shalini Dangi; Divya Teja; Omkar Kabde; Shahid Shafi Dar; Nagendra Kumar (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Multivariate Analysis and Agro-Morphological Characterization of Exotic Cowpea (Vigna unguiculata (L.) Walp.) Germplasm under Indian Agro-Climatic Conditions - Divya Chaudhary; Jyotsna Verma; Dileep Tripathi; Rinky Resma Panda; Rajneesh Kumar; Neeta Singh; Padmavati Ganpat Gore; Ankit Saroha; Dhammaprakash Pandhari Wankhede; Kuldeep Tripathi (Ecological Genetics and Genomics, 2026)

Plant-Mediated CuO Nanoparticles for Reactive Orange Dye Adsorption: Experimental study and Machine Learning-Assisted Optimization - S. Murugeshwari; Madhan Gunasekaran; B. Senthil Rathi; R. M. Saravana Kumar; J. Divya (Water, Air, & Soil Pollution, 2026)

In vitro Evaluation of Antioxidant Capacity: A Review on Screening Assays and Their Analytical Significance - Atla Srinivasa Rao; Gorparthi Nangalya Swathi; Kolli Prabhanjan Kumar; Vattikuti Naga Sai Divya; Borra Venkata Visalakshi; Repakula Naga Ashrith; Neelam Adhi Kesava Naidu (Journal of Pharmaceutical Innovation, 2026)

Axial behavior of circular concrete composites confined with concrete canvas and GFRP - V. M. SharanKarthick; S. Divya; N. Shanmugasundaram; S. Praveen Kumar (Innovative Infrastructure Solutions, 2026)

Harmaline and the gut–brain–immune axis: a novel therapeutic avenue in neuroinflammation and ulcerative colitis - Megha Giri; Swati Arya; Madhuri Grover; Divya Yadav; Srijita Chatterjee; Santosh Kumar Rath (Inflammopharmacology, 2026)

Decoding the PI3K/Akt/mTOR–JAK/STAT signaling axis in multiple sclerosis: mechanistic crosstalk and therapeutic opportunities - Chandrayee Banerjee; Rohit Kumar Singh; Divya Choudhary; MD Nasiruddin Khan; Pankaj Kumar Maurya; Zuber Khan; Sidharth Mehan; Rajaram Samant; Manoj Tongra (Immunologic Research, 2026)

Computational discovery of DENV-3 RdRp allosteric inhibitors: biological evaluation and mechanistic studies - Gokul Krishnan Nagendran; Swati Fageria; Divya Bhatt; Neetu Malya; Akansha Belwal; Shruti Gautam; Muskan Singhal; Ayesha Fatima; Mamta Choudhary; Vineeta Rai; Chetan D. Meshram; Sathish Kumar Mudedla (Molecular Diversity, 2026)

Pollinia storage and viability assessment in Decalepis arayalpathra - S. Gokul; R. K. Divya; Anup S. Deshpande; P. Ravichandran; K. Ravikumar; M. K. Janarthanam; P. E. Rajasekharan; Pradeep Kumar Vishwakarma (Palynology, 2026)

Saccharomyces boulardii in functional food systems: Technological stability, probiotic functionality with microbiome innovation - Deewakar Baral; Eesha Jain; Divya Hemant Choudhary; Rudramadhab Behera; Eshu Sharma; Ashok Kumar Koshariya; Anant Tamang; Aditi Kaushik; Indira Moirangthem; Sajeed Ali (Trends in Food Science & Technology, 2026)

Synthesis of Fe-doped carbon from expired iron supplement tablets coupled with PMS for tetracycline degradation: From a non-radical pathway to an animal survival study - Sabarison Pandiyarajan; Ho-Chiao Chuang; Madan Kumar Arumugam; Divya Rajendran; Nguyen Xuan Sang; Prince Makarios Paul S; Ramanathan Subramanian (Process Safety and Environmental Protection, 2026)

Multiscale attribution of atmospheric methane variability in China using satellite observations and interpretable machine learning - Divya Singh; Jinkai Luan; Hongzheng Zhu; Akshit Kumar; Ning-Xin Wang; Junming Wu; Giri R. Kattel; Zhi-Guo Yu (Journal of Environmental Management, 2026)

Harnessing artificial intelligence in plant breeding: innovations in digital phenotyping and breeding methodologies - Nikita Aggarwal; Mukesh Rathore; Farkhandah Jan; Divya Sharma; Sundeep Kumar; Mahendar Thudi; Abdulqader Jighly; Rajeev K. Varshney; Reyazul Rouf Mir (Theoretical and Applied Genetics, 2026)
Agriculture plays a crucial role in the development of countries whose economies rely heavily on food production. In the face of climate change and growing global population, plant breeders are challenged to adopt more efficient crop improvement strategies. The advances in artificial intelligence (AI), particularly in large-scale data integration, analysis, and pattern recognition, have revolutionized several scientific disciplines, including plant breeding. In this review, we provide a comprehensive survey of the potential of AI tools in plant breeding with four key objectives: (i) revolutionizing high-throughput phenotyping, (ii) exploring AI-driven breeding methodologies beyond traditional approaches, (iii) optimizing breeding pipelines through improved modelling of genotype × environment × management interactions, and (iv) highlighting the limitations of AI in plant breeding and future directions. Case studies published during the past two decades illustrate successful implementations of AI-powered phenotyping and breeding frameworks for major traits across diverse crop species. Furthermore, AI tools show great promise in refining crop traits at the molecular level by increasing the accuracy and precision of emerging fields including gene editing and genomic selection. We emphasize the importance of interdisciplinary collaboration to maximize the benefits of AI in plant breeding programs and to support the sustainable and food-secure future. This review bridges the gap between AI and agricultural applications, offering a roadmap for researchers, industry professionals, and policymakers to harness information fusion and computational models for advancing precision agriculture. It will serve as a valuable resource for future plant breeding, accelerating crop improvement from phenotyping to genomic selection and breeding decision support.

Cost effective industrial scale synthesis of bromo-benzo[b]azepinone: an intermediate for benazepril - Anjan Kumar Nayak; Divya Bajpai Tripathy; Dhananjay Pendharkar; Gaurav Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Melatonin Improves Waterlogging Tolerance in Cowpea Seedlings by Promoting Adventitious Roots, Regulating Polyamines and Nitric Oxide Encoding Genes - Srijan Yadav; Dhirendra Kumar Singh; Akanksha Maurya; Priyanka Kaundal; Divya Singh; Mukul Kumar; Chandra Mohan Singh (Journal of Plant Growth Regulation, 2026)

Co-Administration of LPC and LPS Enhanced the Spinal Cord Vulnerability in a Mouse Model of Focal Demyelination - Divya Goyal; Krutika H. Dobariya; Siddharth Raj; Piyush Maheshkar; Rudra Prasad Naik; Nidhi Singh; Hemant Kumar (Journal of Molecular Neuroscience, 2026)

Spatio-temporal trends of seasonal climate parameters in the Western Himalayan Region - Chitra Kumar; Divya Mehta; Swapnil Rai (Environmental Monitoring and Assessment, 2026)

A 27-year retrospective analysis of 24,633 cases reveals the spectrum of chromosomal abnormalities in Southern India and identifies a novel translocation disrupting EFCAB3 - Usha R. Dutta; Rajitha Ponnala; Kritika Ramgopal; Divya Bhanu Nalla; Uzair Ahmed; Vijay Kumar Sunke; Ashwin Dalal (The Nucleus, 2026)

Multilayered regulation of Fe excess stress and the role of ascorbate in rice - Mayur Patel; Divya Gupta; Raj Kishan Agrahari; Kamiya Takehiro; Petra Bauer; Sanjib Kumar Panda (Protoplasma, 2026)

Integrative Role of OsGGCT2;1 and Glutathione in Regulating Rice Growth and Redox Homeostasis Under Arsenate Stress - Divya Chaudhary; Himanshi Aggarwal; Aman Choudhary; Nischal Pradhan; Richa Vaishnav; Bhoopander Giri; Manoj Kumar; Naveen Chandra Joshi (Journal of Soil Science and Plant Nutrition, 2026)

Prebreeding using untapped rice genetic resources: linking the gap between biodiversity and crop improvement - Santhosh Venna; Divya Balakrishnan; P. K. Singh; B. Arun; Suneetha Kota; S. Amurutha Rao; Naresh Kumar Sahu; S.V. SaiPrasad; R. M. Sundaram (Journal of Crop Science and Biotechnology, 2026)

Impact of coastal pollution on human health: A comparative study on biochemical profile and microbial diversity of coastal and non-coastal populations in Tamil Nadu, India - A. T. Rithi; Jayenth Jayachandran; Abhijit Mitra; Priyadarshini Shanmugam; Alice Peace; Divya Ilanchorian; Antara Banerjee; Arun Kumar Radhakrishnan (Journal of Coastal Conservation, 2026)

Genetic Evaluation of Teak Clonal Seed Orchard for Key Traits Using Linear Mixed Model - Divya Prakash; Naseer Mohammad; Nikhil Verma; Kaushal Tripathi; Pramod Kumar (Indian Journal of Genetics and Plant Breeding, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Bioaccumulation of trace metals in the invasive bivalve Mytella strigata (Hanley, 1843) from estuarine and backwater ecosystems of South India - Shirin Shihab; P.R. Divya; S. Kumaresan; T.T. Ajith Kumar (Marine Pollution Bulletin, 2026)

RNAseq based comparative gene expression reveals early defense activation and involvement of phenylpropanoid pathway in rice root-knot nematode resistance - Premakumar; Divya Singh; Jyoti Yadav; Meghraj Chavhan; Pallavi Mohanapure; Bidwan Rath; Alkesh Hada; Vishal Singh Somvanshi; S Gopala Krishnan; KK Vinod; Prolay K. Bhowmick; Haritha Bollinedi; et al. (Physiological and Molecular Plant Pathology, 2026)

Investigating Fog-Induced Variations in Aerosol Radiative Forcing Over Ranchi, India - Dipanjan Bhattacharjee; Jashvant K. Prasad; Sanat Kumar Das; Swagata Payra; Divya Prakash; Susmita Majumdar (Pure and Applied Geophysics, 2026)

Cloning and Heterologous Expression of Laccase from Beauveria pseudobassiana PHF4 in E. coli and its Application in the Degradation of Catechol - Divya Sharma; Sudha Batta; Ajay Kumar Thakur; Reena Gupta (Current Microbiology, 2026)

Microcystis aeruginosa detected in freshwater lakes in Meghalaya, India show strong hepatotoxicity - Waniabha J. Lyngdoh; Langpoklakpam James Singh; Ankita Dey; Divya Newar; Jopthiaw Nongdhar; Surya Bhan; Arvind Kumar Singh (Archives of Microbiology, 2026)

A review on phosphotungstate-based materials for their photocatalytic degradation - Shivani Devi; Divya Thakur; Amit Kumar; Vivek Sheel; Vinay Chauhan; Deepika Kaushal; Manish Kumar (Next Research, 2026)

Development and evaluation of ‘Quick TB DNA Extraction’ kit for the rapid and efficient detection of multidrug-resistant tuberculosis from sputum transported on bio-safe filter - Rakesh Kumar Gupta; Keerti Chauhan; Ritu Singhal; Divya Anthwal; Vithal Prasad Myneedu; Khalid Umar Khayyam; Sangeeta Choudhary; Ashawant Gupta; Nalini Kant Gupta; Manjula Singh; Jaya Sivaswami Tyagi; Manpreet Bhalla; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Influence of Plant Growth Regulators on Growth, Yield and Fruit Quality of Strawberry Cv. ‘Camarosa’ Under Protected Conditions - Suman Bodh; Jitender Kumar Chauhan; Gopal Singh; Meera Devi; Divya Pandey (Applied Fruit Science, 2026)

Role of FTIR in the physico-chemical characterization of nanoparticles - Amar Kumar; Meenakshi; Divya Sinha; Darshan Singh; Maneesh Kumar Gupta; Nisha Saxena; Kumari Seema; Bablu Kumar; Ghanshyam Upadhyay; Manoj Kumar; Anuradha (Next Research, 2026)

Early immunogenic response to intradermal, subcutaneous, and intramuscular rabies vaccination in cattle and buffaloes: a field study - Divya Sharma; Ashwani Kumar Sharma; Dilip Lakshman; Shrikrishna Isloor (Tropical Animal Health and Production, 2026)

Role of elicitors in secondary metabolites production in Glycyrrhiza glabra L., a highly valued medicinal plant - Divya Jaiswal; Akash Hindangmayum; Devendre Kumar Pandey; Kandregula Sowjanya Sree; Padmanabh Dwivedi (The Nucleus, 2026)

Relative fitness cost in Aedes aegypti L. (Diptera: Culicidae) on treatment with diflubenzuron and diflubenzuron/verapamil combination - Manu Sankar; Vinay Singh Dagar; Divya Yadav; Sarita Kumar (International Journal of Tropical Insect Science, 2026)

Microbial metabolites–-a sustainable solution for agricultural challenges: A review - Rajat SINGH; Priyanka SONI; Rajul JAIN; Akash CHAUHAN; Rahul KUMAR; Divya GUNSOLA; Sourav CHATTARAJ; Sergio DE LOS SANTOS-VILLALOBOS; Debasis MITRA; Ashish GAUR (Pedosphere, 2026)

Assessment and Monitoring of Hydrological and Groundwater Quality In and Around Sugar Factory: A comprehensive Study - Divya Patel; Ananthalakshmi Ranganathan; Seema Paroha; Anoop Kumar Kanaujia (Sugar Tech, 2026)

Differential Response of Maize Genotypes to Phosphorous Deficiency and Mitigation by Pseudomonas putida Via Fatty Acid and Nitrogen Metabolism - Tanya Singh; Nikita Bisht; Divya Prakash; Mohd. Mogees Ansari; Shashank Kumar Mishra; Puneet Singh Chauhan (Journal of Plant Growth Regulation, 2026)

Regional distribution and seasonal histomorphology of cell types of pars distalis adenohypophysis of Gaddi goats: A comparative study between the year 2001 and the present in the context of climate change - Arjun Kumar Rao; Virender Pathak; Rajesh Rajput; Divya Gupta; Parul Shukla (Tropical Animal Health and Production, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Exploring progenitor and non-progenitor derived wheat introgressions for Karnal bunt resistance - Anju Grace George; Ritu Bala; Vineet Kumar Sharma; Habiburahman Ayoubi; Divya Bhandhari; Puja Srivastava; Jaspal Kaur; Yogita Bohra; Satinder Kaur (Genetic Resources and Crop Evolution, 2026)

Deep learning of seasonal peak snow water content of global boreal forest and arctic using spaceborne L-band radiometry - Divya Kumawat; Ardeshir Ebtehaj; Sujay Kumar; Andreas Colliander (Remote Sensing of Environment, 2025)

Targeting neurotrophic dysregulation in diabetic retinopathy: a novel therapeutic avenue - Divya Rana; Sanchit Dhankhar; Rupali Chauhan; Monika Saini; Randhir Singh; Parveen Kumar; Thakur Gurjeet Singh; Samrat Chauhan; Sushma Devi (Molecular Biology Reports, 2025)

Exploring loose smut resistance in Indian wheat germplasm: marker-linked insights to postulate resistance genes - Divya Bhandhari; Ritu Bala; Puja Srivastava; Jaspal Kaur; Vineet Kumar Sharma (Cereal Research Communications, 2025)

Novel Efficient Genome-Wide STR Panels for the Conservation of the Endemic Catfishes of Western Ghats: Critically Endangered Hemibagrus punctatus Jerdon (1849) and Vulnerable Horabagrus brachysoma (Günther, 1864) - P. R. Divya; Divya Merin Jose; Magdeline Christo; Charan Ravi; Uttam Kumar Sarkar (Biochemical Genetics, 2025)

Association of Urine Heavy Metals with Prevalence of Type 1 Diabetes and Poor Glycaemic Control - Samrat Ashok Vasudevan; Srinidhi Narayani Seenivasan; Avinash Kumar Raghupathy; Dinakaran Vasudevan; Parthasarathy Ayothi; Tanmayaa Nayak; Buvaneswari Gajendran; Karthika Durairaj; Divya Shree Sathish; Srilaxmi Balaji; Abisheak Kandasamy; P. Amaravathy; et al. (Biological Trace Element Research, 2025)

Systematic review on carbon and biodiversity in forest ecosystems of Amazonia - Divya Mehta; Ciro Abbud Righi; Chitra Kumar; Carlos Rodrigues Pereira (Environmental Monitoring and Assessment, 2025)

Role of Fibroblast Growth Factors in Neurological Disorders: Insight into Therapeutic Approaches and Molecular Mechanisms - Shubham Upadhayay; Divya Soni; Maanvi Dhureja; Pooja Temgire; Vishal Kumar; Richmond Arthur; Puneet Kumar (Molecular Neurobiology, 2025)

Cu-catalyzed click reaction in synthesis of eugenol derivatives as potent antimalarial agents - Jyoti; Divya Bhatt; Saurabh Kumar; Aransha Maurya; Anirban Pal; Mahendra P. Darokar; Dnyaneshwar U. Bawankule; Sudeep Tandon (Natural Product Research, 2025)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Phenserine Mitigates Neuroinflammation, Apoptosis, and Behavioural Deficits to Enhance Motor Function and Recovery in a Mouse Model of Spinal Cord Injury - Lahanya Guha; Divya Goyal; Nidhi Singh; Mamidi Teena; Inbo Han; Hemant Kumar (Molecular Neurobiology, 2025)

Isolation and characterization of xyloglucan endotransglucosylase/hydrolase (XET/XTH) provide insights on the functional evolution of XET family proteins in ginger (Zingiber officinale Roscoe) - Arshya Devi; Divya P. Syamaladevi; B. Mekha; K. S. Nehamol; I. P. Vijesh Kumar; T. E. Sheeja; D. Prasad (Genetic Resources and Crop Evolution, 2025)

Neuroinflammation and acetylcholinesterase inhibition potentials of acyclic monoterpenoids isolated from Cymbopogon distans (Nees ex Steud.) Will. Watson - Swati Singh; Divya Bhatt; Munmun Kumar Singh; Suyashi Mishra; Uma Shankar; Aransha Maurya; Rajendra Chandra Padalia; Sudeep Tandon; Dnyaneshwar Umrao Bawankule; Ram Swaroop Verma (Natural Product Research, 2025)

Priming-a state of alert against environmental stress challenges in plants - Divya Chaudhary; Himanshi Aggarwal; Banpreet Kaur; Himani Agarwal; Arghyabrata Das; Ajay Kumar; Vaibhav Mishra; Prashant Kumar Singh; Naveen Chandra Joshi (Plant Gene, 2025)

Deciphering the accumulation of potentially toxic metals and their relation with size in the five commercially important fish species from the middle stretch of the River Ganga - Mohammed Aasif Sulaiman; Mohammad Masroor Zafar; Divya; Saima Anjum; Kumar Gaurav; Ravindra Kumar Sinha; Anupma Kumari (Next Research, 2025)

Metabolic dysregulation and temporal dynamics of NF-κB-p65/NLRP3, TXNIP, endoplasmic reticulum and mitochondrial stress in silica-induced pulmonary fibrosis in rats - Kaveri R. Washimkar; Chirag Kulkarni; Manendra Singh Tomar; Shobhit Verma; Divya Bhatt; Smriti Verma; D.V. Siva Reddy; Baisakhi Moharana; Amit Misra; Dnyaneshwar U. Bawankule; Srikanta Kumar Rath; Naibedya Chattopadhyay; et al. (Journal of Hazardous Materials, 2025)

Unveiling the possible causes of July 2023 unprecedented flood in National Capital Territory of Delhi, India - Omvir Singh; Jyoti Sharma; Ajay Kumar; Divya Saini (Natural Hazards, 2025)

Leaf miRNAs of Withania somnifera Negatively Regulate the Aging-Associated Genes in C. elegans - Shilpi Yadav; Ravi Kr. Gupta; Sailendra Kumar; Anamta Rizvi; Divya Tyagi; Aruna Satish; Digvijay Verma; Akanksha Vishwakarma; Sangeeta Saxena (Molecular Neurobiology, 2025)

Late Quaternary productivity and hydrographic variability in the upper water column of the Agulhas Return Current region as inferred from planktic foraminifera - Divya Verma; Pawan Govil; Shailesh Agrawal; P. Morthekai; Brijesh Kumar; Hidayatullah Khan (Quaternary International, 2025)

Evaluation of machine-learning algorithms in estimation of relative water content of sorghum under different irrigated environments - S. Divya Dharshini; Anurag; Anil Kumar; Satpal; Manoj Kumar; P. Priyanka; K. Pugazenthi (Journal of Arid Environments, 2025)

The Impact of Quality of Sleep and Effect of Sleep Apnea on Periodontal Health - Swathi Devarajan; P. Sreelakshmi; Divya Kumar; Deepak Moses Ravindran; Dhanadivya Krishnakumar; S. K. Balaji (Sleep and Vigilance, 2025)

Component identification of solid biomass fuels using reflected light microscopy: Interlaboratory study 2 - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Menandro N. Acda; Tushar Adsul; Neža Malenšek Andolšek; Lorenzo Animali; Omid H. Ardakani; Telma Ataide; Demberelsuren Batbold; Mohd Younus Bhat; et al. (International Journal of Coal Geology, 2025)

Treatment of Chlorinated Volatile Organic Compounds Using Different Bioreactor Systems: Microbial Communities and Pollutant Removal - Divya Baskaran; Shishir Kumar Behera; Biswanath Mahanty; Mansi Aliveli; Amira Elmanadely; Abubakar M. Bilyaminu; Anina James; Eldon R. Rene; Ravi Rajamanickam (Water, Air, & Soil Pollution, 2025)

Elucidating neural molecular mechanisms underlying metabolic disorders-induced neuropsychiatric disorders in mice on prolonged high fructose diet - Sachin Singh; Nitesh Kumar Singh; Kottapalli Srividya; Unis Ahmad Bhat; Divya Tej Sowpati; Sumana Chakravarty; Arvind Kumar (Metabolic Brain Disease, 2025)

Renoprotective activity of micellar nanoformulations versus crude extracts in type 2 diabetic SD rats with preliminary GC–MS and LC-MS Profiling - Unnam Sambamoorthy; Renuka devi thota; Sunil Kumar Panda; Divya Amaravadi; Nimra Mujeeb; Uttam Prasad Panigrahy; Yaso Deepika Mamidisetti; Venkataiah Gudise (Next Research, 2025)

Decarboxylative click cycloaddition: an emerging strategy towards substituted 1,2,3-triazole derivatives - Manpreet Kaur; Divya Bharti; Vinod Kumar; Praveen Kumar Verma; Rakesh Kumar (Molecular Diversity, 2025)

Plant Defense Hormones: Thermoregulation and Their Role in Plant Adaptive Immunity - Zahoor Ahmad Mir; Sajad Ali; Subaya Manzoor; Divya Sharma; Deepak Sharma; Anshika Tyagi; Ab Waheed Wani; Sundeep Kumar; Belay T. Ayele (Journal of Plant Growth Regulation, 2025)

Evaluation of Eclipta alba L. selections for higher biomass and bioactive compound - K. Hima Bindu; K. Keshav Rao; Shiva Kumar; B. Anil Kumar; R. M. Shalini; Priti Sonavane; K. S. Divya; S. Sujatha (Genetic Resources and Crop Evolution, 2025)

Morphological variability and genetic diversity assessment of agronomic traits in cowpea (Vigna unguiculata (L.) Walp.) core collection using multivariate analysis - Divya Chaudhary; Padmavati Ganpat Gore; Dhammaprakash Pandhari Wankhede; Deepak Khanderao Patil; Shashi Bhushan Choudhary; Annabathula Mohan Rao; Raj Kumar Gautam; Gyanendra Pratap Singh; Kuldeep Tripathi (Genetic Resources and Crop Evolution, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Sustainable Agriculture in Food Security Integrating Satellite Data Risk Assessment by Cyberattack Detection: AI Applications - M. Prema Kumar; N. Krishnammal; Manu Gupta; Mairaj Unisa Begum; Sameera Sultana; Divya Priya Degala (Remote Sensing in Earth Systems Sciences, 2025)

Influence of fibre ratio and chemical treatment on the properties of hybrid epoxy composites reinforced with areca and banana fibre - Subramanya Raghavendra; Chandra Shekar A; Manjunatha KN; Suresha S; Madhusudhana SV; Arun Kumar R; Prabhakara SS; Divya SN; Satish Kumar KB; Raveendra RS (Journal of the Indian Academy of Wood Science, 2025)

Effect of integrated disease management modules against major diseases (bacterial blight/root rot and downy mildew) of opium poppy - Shivam Singh; R. S. Mishra; S. K. Singh; M. K. Maurya; J. R. Yadav; Divya Singh; Abhishek Kumar; V. V. Raghuvanshi (Vegetos, 2025)

Assessment and monitoring of uranium contamination in Champawat District of Uttarakhand, India: a comprehensive study - Kiran Patni; Ashutosh Pratap Pande; Divya Patel; Chitra Pande; Ajay Kumar (Environmental Science and Pollution Research, 2025)

Assessment of Spring Water Hydrogeochemistry in the Intermountain Doon Valley of the Himalayan Region Using Water Quality Indexing and Multivariate Statistical Methods - Kanchan Deoli Bahukhandi; Bartarya S.K; Vishal Kamboj; Uday Bhan; Lalit Goswami; Anamika Kushwaha; Seungdae Oh; Divya Thakur; Vipin Kumar Saini; Nitin Kamboj; Bhavtosh Sharma; Pankaj Mewarguru (Water, Air, & Soil Pollution, 2025)

Natural products as drug leads: exploring their potential in drug discovery and development - Kuldeep Singh; Jeetendra Kumar Gupta; Dilip Kumar Chanchal; Manoj Gangadhar Shinde; Shivendra Kumar; Divya Jain; Zainab M. Almarhoon; Asma M. Alshahrani; Daniela Calina; Javad Sharifi-Rad; Anjali Tripathi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

GGE biplot analysis for cane yield and sugar yield in advanced clones of sugarcane (Saccharum sp. complex) - Divya Chaudhary; Anand Singh Jeena; Narendra Kumar Singh; Usha Pant; Rohit Rohit; Sonali Gaur (Journal of Applied Genetics, 2025)

Detection of Tilapia parvovirus in farm-reared tilapia in India and its isolation using fish cell lines - Allahbagash Badhusha; Sivaraj Mithra; Gani Taju; Venkatesan Rajkumar; Seepoo Abdul Majeed; Selvam Suryakodi; Lekshmi Haridas; Divya Haridas; Pramoda Kumar Sahoo; Jyotirmaya Mohanty; Anirban Paul; Snatashree Mohanty; et al. (In Vitro Cellular & Developmental Biology - Animal, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

Population frequency distribution and introgression of Alternaria species causing leaf blight of sunflower, India - Divya shree; C.P. Manjula; M.K. Prasanna Kumar; K.B. Palanna; J. Harish; Pasumarthi Venkata Dinesh Kumar; Farooq khan (Physiological and Molecular Plant Pathology, 2025)

Effective Biomixture for Preventing Pesticide Point Source of Contamination - Kumari Divya Jyoti; Pritam Ganguly; Arnab Goon; Munna Kumar; Rajat Kumar Roy; Arvind Kumar; Mainak Ghosh; Rajiv Rakshit (Journal of Soil Science and Plant Nutrition, 2025)

A Comprehensive Review on Plant-Based Medications and Chemical Approaches for Autism Spectrum Disorders (ASDs) Psychopharmacotherapy - Vrish Dhwaj Ashwlayan; Ratneshwar Kumar Ratnesh; Divya Sharma; Alok Sharma; Akansha Sangal; Alimuddin Saifi; Jay Singh (Indian Journal of Microbiology, 2025)

Phase equilibria modelling, fluid inclusion study, and U-Pb zircon dating of ultra-high temperature mafic granulites from Rampur domain, Eastern Ghats province: implications for the Indo-Antarctic correlation - Divya Prakash; Rajeev Kumar Pandey; Saurabh Singh; Chandra Kant Singh; Manish Kumar; Bikash Mahanta; Aditya Kharya; Himanshu K. Sachan; Kamesh Sharma (Contributions to Mineralogy and Petrology, 2025)

Adequate Levels of Zinc and Copper on Turkey Poult Performance, Immunological Response, and Skeletal Health - Jayanti L Agashe; Chandra Deo; Avishek Biswas; Divya Sharma; Mukesh T Nampalle; Ashok Kumar Tiwari (Biological Trace Element Research, 2025)

Western equatorial Indian Ocean surface hydrographic variations inferred from isotopic record of planktic foraminifera Globigerinoides ruber during last ~412,000 years - Brijesh Kumar; Pawan Govil; Shailesh Agrawal; Pankaj Kumar; Divya Verma; Hidayatullah Khan (Journal of Earth System Science, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Photocatalytic degradation of trimethoprim and growth inhibition of pathogens using g-C3N4/AgMoO4 heterojunction catalyst - Yadav Sneha; Thinley Tenzin; Divya Vinod; Mudassar Shahid; Ramith Ramu; David Jenkins; Sumana Kumar; Harikaranahalli Puttaiah Shivaraju (Journal of Water Process Engineering, 2025)

Ultrahigh-temperature granulites from the Shillong-Meghalaya Gneissic Complex, NE India: Implications for the Indo-Antarctic Correlation - Bikash Mahanta; Divya Prakash; Manish Kumar; Saurabh Singh; Rajeev Kumar Pandey; Chandra Kant Singh; Roopali Yadav; Jesus Solé Vinas (Journal of Asian Earth Sciences, 2025)

Characterizing metabolome signature of colostrum, transition and mature milk of indigenous cows (Bos indicus) adapted to high altitude environment of Leh-Ladakh - Amarjeet; Umesh Kumar; Monika Sodhi; Dinesh Kumar; Prince Vivek; Saket K. Niranjan; Ranjit Singh Kataria; Sudarshan Kumar; Manish Sharma; Manish Tiwari; Rajeev A.K. Aggarwal; Vijay K. Bharti; et al. (Food Chemistry, 2025)

Fluorine-substituted bifunctional molecules for enhanced perovskite solar cell performance - Murali Ravi; Mengde Zhai; Ziyang Xia; Cheng Chen; Haoxin Wang; Yi Tian; Divya Kumar; Abisharani Johnson Mary Leeda Rani; Ming Cheng (Chemical Engineering Journal, 2025)

Arsenic removal using de-oiled mentha biomass biochar: Adsorption kinetics and the role of iron modification - Sampurna Nand; Saroj Kumar; Bhanu Pratap; Divya Dubey; Mariya Naseem; Anju Patel; Siddharth Shukla; Pankaj Kumar Srivastava (Journal of Cleaner Production, 2024)

Operational feasibility and multi-centric evaluation of ‘TB Detect sputum microscopy kit’ for the direct detection of Mycobacterium tuberculosis in field settings - Keerti Chauhan; Rakesh Kumar Gupta; Divya Anthwal; Nikita Panwalkar; Prabha Desikan; Manpreet Bhalla; Ritu Singhal; Vithal Prasad Myneedu; Khalid Umar Khayyam; Siva Kumar Shanmugam; K. Silambu Chelvi; A. Radhakrishnan; et al. (Infectious Diseases, 2024)

Contraceptives Association with Vaginal Microbiome and RTI: A Cross-Sectional Survey in Females of Jammu and Kashmir, India - Chitrakshi Chopra; Divya Sharma; Vinay Kumar; Indu Bhushan (Indian Journal of Microbiology, 2024)

Remote Sensing–Based UAV Imaging in Heat Pattern Analysis Impact on Climate Change Detection Using Fuzzy Stacked Lasso Elastic-Net Model - M. Sailaja; M. Prema Kumar; B. Swarna Jyothi; G. L. Narasamba Vanguri; S. Manjula; D. Divya Priya (Remote Sensing in Earth Systems Sciences, 2024)

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Identification and pathogenicity of mycoflora associated with leaf spot disease of Aloe vera - Divya Singh; V. P. Chaudhary; S. K. Singh; Shivam Singh; Jay Kumar Yadav; Harshita (Vegetos, 2024)

Seaweed extracts: enhancing plant resilience to biotic and abiotic stresses - Gagan Kumar; Satyabrata Nanda; Sushil Kumar Singh; Sanjeet Kumar; Divya Singh; Bansh Narayan Singh; Arpan Mukherjee (Frontiers in Marine Science, 2024)
Seaweeds are a natural marine resource containing many bioactive compounds such as amino acids, lipids, carbohydrates, proteins, phytohormones, and antimicrobial compounds. Since ancient times, seaweeds have been used in various sectors, including medicine, food, and the cosmetic industry. Currently, seaweeds are a promising alternative to reduce the application of harmful chemicals in agriculture. Seaweed and its derived products have been utilized for plant growth promotion, immunity enhancement, and the reduction of biotic and abiotic stresses. In the current global scenario, synthetic fertilizers and chemical pesticides are commonly used to increase agricultural crop production to meet the growing demands of the world population. However, these chemicals pose significant threats to the health of people, livestock, plants, soil, and the entire environment. In contrast, seaweed-based products are emerging as a newer option for stress mitigation and reduction, offering an alternative to synthetic chemicals. This article explains the use of seaweed extracts to increase the tolerance of plants to biotic and abiotic stresses. We also address the functions of various bioactive compounds present in seaweed extracts and the mechanisms by which they promote plant growth and induce defense against different stresses.

Application of artificial intelligence tools in wastewater and waste gas treatment systems: Recent advances and prospects - Shishir Kumar Behera; S. Karthika; Biswanath Mahanty; Saroj K. Meher; Mohd. Zafar; Divya Baskaran; Ravi Rajamanickam; Raja Das; Kannan Pakshirajan; Abubakar M. Bilyaminu; Eldon R. Rene (Journal of Environmental Management, 2024)

Gene Editing: Paving the Way for Enhancing Plant Tolerance to Abiotic Stresses-Mechanisms, Breakthroughs, and Future Prospects - Divya Gupta; Amita Saini; Christell van der Vyver; Sanjib Kumar Panda (Journal of Plant Growth Regulation, 2024)

Land use and altitudinal variability in biomass and carbon storage potential in mid-hill and sub-humid conditions of north-western Himalayas - Priyanka Rajput; D. R. Bhardwaj; Jatin Kumar; Saakshi; Prashant Sharma; Aalok Gulabrao Yewale; Divya Khatri (Environment, Development and Sustainability, 2024)

Plant biomass-based nanoparticles for remediation of contaminants from water ecosystems: Recent trends, challenges, and future perspectives - Divya Bhushan; Sachin Shoran; Rakesh Kumar; Renuka Gupta (Chemosphere, 2024)

Assessment of species migration patterns in forest ecosystems of Tamil Nadu, India, under changing climate scenarios - Ramachandran A.; Mithilasri Manickavasagam; Hariharan S.; Mathan M.; Ahamed Ibrahim S.N.; Divya Subash Kumar; Kurian Joseph (Theoretical and Applied Climatology, 2024)

Insights to therapeutic potentials, pharmaceutical formulations, chemistry and analytical methods of catechin - Divya Shikha; Amandeep Singh; Naresh Kumar Rangra; Vikramdeep Monga; Rohit Bhatia (Phytochemistry Reviews, 2024)

Crosstalk between gut–brain axis: unveiling the mysteries of gut ROS in progression of Parkinson’s disease - Divya Soni; Shubham Upadhayay; Maanvi Dhureja; Richmond Arthur; Puneet Kumar (Inflammopharmacology, 2024)

Quantifying abnormal writing kinematics in writer’s cramp using a novel software platform - Kavadisseril Vivekanandan Vysakha; Vineeth Radhakrishnan; Praveen James; B. Suresh Kumar; Ashish Anand Susvirkar; Gangadhara Sarma; Ajith Cherian; K. P. Divya; Syam Krishnan Nair; Asha Kishore (Acta Neurologica Belgica, 2024)

A circular economy approach for sustainable water reuses in India: policies, practices and future prospects - Divya Dubey; Saroj Kumar; Venkatesh Dutta (Environmental Sustainability, 2024)

Himalayan phytochemicals and their role as epigenetic modulating agents in cancer, diabetes and neurodegenerative disorders - Shubham Kumar; Jasdeep Singh; Vagish Dwibedi; Swati; Divya Singhal; Swati Sharma (Vegetos, 2024)

A Comprehensive Insight into the Pharmaceutical Potential of Saussurea obvallata - Nabarun Mukhopadhyay; Divya Jain; Anjali Tripathi; Amith Kumar B; Pranav Bhaskar (Current Pharmacology Reports, 2024)

Enhancing milk quality assessment with watermelon (Citrullus lanatus) urease immobilized on VS2-chitosan nanocomposite beads using response surface methodology - Prince Kumar; Divya; Amit Kumar Patel; Anchal Srivastava; Arvind M. Kayastha (Food Chemistry, 2024)

Assessment of thermal damage for plasmonic photothermal therapy of subsurface tumors - Amit Kumar Shaw; Divya Khurana; Sanjeev Soni (Physical and Engineering Sciences in Medicine, 2024)

ReDtool: a Python-based command line tool for restriction digestion analysis of large DNA sequences - Guntha Shiva Brahmam; Divya Mishra; Vikash Kumar Yadav (Journal of Plant Biochemistry and Biotechnology, 2024)

Ni-Zn/CeO2 nanocomposites for enhanced adsorptive removal of 4-chlorophenol - Nitish Semwal; Divya Mahar; Manjunath Chatti; Rajesh Kumar; Mahesh Chandra Arya (Environmental Science and Pollution Research, 2024)

Identification of hub genes associated with stripe rust disease in wheat through integrative transcriptome and gene-based association study - Divya Chauhan; Dwijesh Chandra Mishra; Shikha Mittal; Sushma Rani; Jyotika Bhati; Sundeep Kumar; Subhash C. Bhardwaj; Monendra Grover; Neeraj Budhlakoti; Suphiya Khan (South African Journal of Botany, 2024)

An eco-friendly approach harnessing Trichoderma lixii ORT2 for reducing chemical phosphatic fertilizer dependency and groundwater phosphorus management through integrated in silico, in vitro and omic studies - Shalini Tiwari; Barkha Sharma; Seema Bisht; Divya Pant; Sunil Kumar; Lakshmi Tewari (Groundwater for Sustainable Development, 2024)

A concise review of the impact of groundwater pollution in coastal regions on human gut microbiome composition and its effect on human health - Rithi A T; Antara Banerjee; Abhijit Mitra; Keerthi Nethaji; Divya Ilanchoorian; Arun Kumar Radhakrishnan (Groundwater for Sustainable Development, 2024)

Hazard identification of endocrine-disrupting carcinogens (EDCs) in relation to cancers in humans - Neha Sharma; Vinay Kumar; Vimal S.; Mridul Umesh; Preeti Sharma; Basheer Thazeem; Komalpreet Kaur; Jithin Thomas; Ritu Pasrija; Divya Utreja (Environmental Toxicology and Pharmacology, 2024)

Pharmacology of Manilkara hexandra leaf extract: potent antimalarial by targeting β-hematin formation and pro-inflammatory cytokine investigation - Ravi Kumar; Saurabh Kumar; Parmanand Kumar; Divya Bhatt; Deepika Srivastava; Narendra Kumar; D. U Bawankule; Anirban Pal (Vegetos, 2024)

Antimicrobial resistance landscape in a metropolitan city context using open drain wastewater-based metagenomic analysis - Manas Kumar Madhukar; Nirupama Singh; V Rajesh Iyer; Divya Tej Sowpati; Karthik Bharadwaj Tallapaka; Rakesh Kumar Mishra; Shivranjani Chandrashekhar Moharir (Environmental Research, 2024)

Time–frequency characterization of seasonal temperature in India and teleconnection of temperature with atmospheric oscillation indices - Hareesh Kumar; Nitin Joshi; Himanshu Sharma; Divya Gupta; Shakti Suryavanshi (Stochastic Environmental Research and Risk Assessment, 2024)

Fine mapping of interspecific secondary CSSL populations revealed key regulators for grain weight at qTGW3.1 locus from Oryza nivara - Malathi Surapaneni; Divya Balakrishnan; Krishnamraju Addanki; Venkateswara Rao Yadavalli; Arun Prem Kumar; P. Prashanthi; R. M. Sundaram; Sarla Neelamraju (Physiology and Molecular Biology of Plants, 2024)

Geochemical and geochronological evolution of the UHT granulites from the Eastern Ghats Mobile Belt, India: implications from F-OH substitution in biotite, thermal events and cooling age - Saurabh Singh; Divya Prakash; Roopali Yadav; Manish Kumar; Bikash Mahanta; Jesús Solé Viñas (International Geology Review, 2024)

Proteome profile of nucleus accumbens (NAc) uncovers the differential and sex-specific role of CRMP2 in CVMS-induced mouse model of depression - Bhanu Chandra Karisetty; Divya Duscharla; Vincy Vijay; Shashikant Patel; Kalyani Soren; Arvind Kumar; Ramesh Ummanni; Sumana Chakravarty (Journal of Proteins and Proteomics, 2024)

Evaluation of in-feed supplementation of formic acid and thymol as non-antibiotic growth promoters and assessing their effect on antimicrobial resistant E.coli isolated in Turkey - Abhijeet Champati; Subrat Kumar Bhanja; Jaydip Jaywant Rokade; Nibedita Nayak; Ajit Singh Yadav; Avishek Biswas; Divya Sharma; Juli Chakma; Sky; Jyotiprabha Mishra; Subodh Kumar Saha; Ravi Kant Agrawal; et al. (Veterinary Research Communications, 2024)

Meticulous Taxonomic Evidence and Molecular Confirmation of Sphyraena forsteri Cuvier, 1829 (Carangiformes: Sphyraenidae) from the Southeast coast of India - Sivaranjani Sekar; Kannan Karuppiah; Kumar Rajendran; Madhuri Krishnamoorthy; Divya Dharmaraj; Kannapiran Ethiraj (Thalassas: An International Journal of Marine Sciences, 2024)

Biochar supported Ag/Cu-ZrO2 nano-hetero assembly for enhanced adsorption of heavy metal ions and biomedical applications - Deepak Pathania; Ajay Kumar; Adesh K. Saini; Reena Saini; Divya Mittal; Arush Sharma (Nanotechnology for Environmental Engineering, 2024)

SIRT6 in Regulation of Mitochondrial Damage and Associated Cardiac Dysfunctions: A Possible Therapeutic Target for CVDs - K. P. Divya; Navjot Kanwar; P. V. Anuranjana; Gautam Kumar; Fathima Beegum; Krupa Thankam George; Nitesh Kumar; K. Nandakumar; Abhinav Kanwal (Cardiovascular Toxicology, 2024)

Fluoride contamination in groundwater of the middle Gangetic plains of India: A comparative geochemical and health risk assessment. - Mohammed Aasif Sulaiman; Mohammad Masroor Zafar; Divya; Kumar Gaurav; Anupma Kumari (Groundwater for Sustainable Development, 2024)

Linum usitatissimum mediated green synthesis of Cu3V2O8 nanoparticles and its photocatalytic activity studies - Divya R. Basavannavar; Kunal Mohan Mishra; Adheena Biju; E. Vinay kumar; J.R. Naveen Kumar; B.M. Praveen; G. Nagaraju (Environmental Nanotechnology, Monitoring & Management, 2024)

Development of novel microsatellite markers for aquaculture important species, milkfish (Chanos chanos Forsskål, 1775) with implications of conservation and management - Divya Merin Jose; Divya Prema Radhakrishnan; Kuldeep Kumar Lal (Conservation Genetics Resources, 2024)

Bioengineering of Cu2O structured macro-biotemplate for the ultra-efficient and selective hand-retrieval of glyphosate from agro-farms - Divya S. Parimi; M.V. Jyothirmai; Mahesh Kumar Ravva; Amit K. Jaiswal; Anil K. Suresh (Science of The Total Environment, 2024)

Abrupt intensification of AMOC and monsoonal winds during mid-MIS4 (Heinrich Event 6) in the western Arabian Sea - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Shailesh Agrawal; Pankaj Kumar; Brijesh Kumar; Divya Verma (Global and Planetary Change, 2024)

Widening the clinical, radiological and genetic spectrum of autosomal recessive ataxia of Charlevoix-Saguenay in Indian patients - K. P. Divya; Ajith Cherian; Hemanga Kumar Dhing; Savith Kumar; Bejoy Thomas; Mohammed Faruq (Acta Neurologica Belgica, 2024)

First report of clinically significant bites due to Platyceps ventromaculatus (GRAY, 1834) from Thar Desert region, Rajasthan, India - Akhilesh Kumar; Sourish Kuttalam; Divya Tanwar; Bharat Choudhary; Mahendra Kumar Garg; Maya Gopalakrishnan (Toxicon, 2024)

Extreme wave height response to climate modes and its association with tropical cyclones over the Indo-Pacific Ocean - Prashant Kumar; Anshu Yadav; Divya Sardana; Ramakant Prasad; Rajni (Ocean Engineering, 2024)

Impact of urbanization and temperature on local abundance of Drosophila repleta Wollaston (1858) in the Western Himalayas - Seema Ramniwas; Girish Kumar; Manish Pandey; Divya Singh (Journal of Asia-Pacific Entomology, 2024)

CMIP6 model evaluation for sea surface height responses to ENSO - Divya Sardana; Prashant Kumar; Rajni (Climate Dynamics, 2024)

CMIP6 Model Evaluation for Mean and Extreme Precipitation Over India - Prabha Kushwaha; Vivek Kumar Pandey; Prashant Kumar; Divya Sardana (Pure and Applied Geophysics, 2024)

Acyclic monoterpenoid-rich essential oil of Cymbopogon distans mitigates skin inflammation: a chemico-pharmacological study - Divya Bhatt; Swati Singh; Munmun Kumar Singh; Anil Kumar Maurya; Amit Chauhan; Rajendra Chandra Padalia; Ram Swaroop Verma; Dnyaneshwar U. Bawankule (Inflammopharmacology, 2024)

Influence of climate variability modes over wind-sea and swell generated wave energy - Divya Sardana; Prashant Kumar; Rajni (Ocean Engineering, 2024)

Callus induction and efficient in vitro plant regeneration protocol for Chickpea - Vinod Kumar Jangid; Muthappa Senthil-Kumar; Divya Chandran; Senjuti Sinharoy (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Production performance, haematological parameters, serum biochemistry, and expression of HSP-70 in broiler chickens fed dietary ascorbic acid during heat stress - Avishek Biswas; Chandra Deo; Divya Sharma; Ansari Matin; Ashok Kumar Tiwari (International Journal of Biometeorology, 2024)

Direct Detection of Fluoroquinolone Resistance in Sputum Samples from Tuberculosis Patients by High Resolution Melt Curve Analysis - Rakesh Kumar Gupta; Divya Anthwal; Manpreet Bhalla; Jaya Sivaswami Tyagi; Sangeeta Choudhary; Sagarika Haldar (Current Microbiology, 2024)

Sustainable SMART fertilizers in agriculture systems: A review on fundamentals to in-field applications - Divya Shanmugavel; Iryna Rusyn; Omar Solorza-Feria; Sathish-Kumar Kamaraj (Science of The Total Environment, 2023)

Prevalence of extended spectrum β-lactam, methicillin, and vancomycin resistant zoonotic bacterial pathogens in milk - Raghu Vishweswaraiah; Divya Sharma; Mehak Mehta; Avinash Jaswal; Kriti Dua; Rashmi Mallappa; Diwas Pradhan; A.S. Mariya Divanshi; Gurjinder Kaur; Naresh Kumar; Anil Kumar Puniya (Food and Humanity, 2023)

Meta-QTL analysis in wheat: progress, challenges and opportunities - Divya Sharma; Anita Kumari; Priya Sharma; Anupma Singh; Anshu Sharma; Zahoor Ahmad Mir; Uttam Kumar; Sofora Jan; M. Parthiban; Reyazul Rouf Mir; Pradeep Bhati; Anjan Kumar Pradhan; et al. (Theoretical and Applied Genetics, 2023)

Drought stress in maize: stress perception to molecular response and strategies for its improvement - Ashutosh Singh; Himanshu Pandey; Saurabh Pandey; Dalpat Lal; Divya Chauhan; Aparna; Suresh H. Antre; Santhosh B; Amarjeet Kumar (Functional & Integrative Genomics, 2023)

Anthropogenic disturbances influence mineral and elemental constituents of freshwater lake sediments - Divya Dubey; Saroj Kumar; Venkatesh Dutta (Environmental Monitoring and Assessment, 2023)

Effects of Various Copper Sources and Concentrations on Performance, Skeletal Growth, and Mineral Content of Excreta in Broiler Chickens - Chandra Deo; Avishek Biswas; Divya Sharma; Jayanti L. Agashe; Ashok Kumar Tiwari (Biological Trace Element Research, 2023)

Co-exposure of microplastics and heavy metals in the marine environment and remediation techniques: a comprehensive review - Punmoth Kalyadan Vrinda; Radhakrishnan Amal; Nandakumar Abhirami; Divya Alex Mini; Vattiringal Jayadradhan Rejish Kumar; Suja Purushothaman Devipriya (Environmental Science and Pollution Research, 2023)

Dissecting the Relationship Between Neuropsychiatric and Neurodegenerative Disorders - Rohan Gupta; Dia Advani; Divya Yadav; Rashmi K Ambasta; Pravir Kumar (Molecular Neurobiology, 2023)

Synthesis, in-silico based virtual screening,anti-cancer potential of novel1,2,3-triazole-thiadiazole hybrid derivatives as Aurora kinase A (ARK-A) and Extracellular regulated kinase 2 (ERK2) dual inhibitors - Lingaiah Bontha; Praveen Kumar Edigi; Appaji Dokala; Divya Pingili; Venkat Reddy Putta; Ravi kumar Vuradi; Laxma Reddy Kotha; Satyanarayana Sirasani (Medicinal Chemistry Research, 2023)

Microbial fuel Cell-based Co-generation system for bioethanol production and power management solution - Akansha Shrivastava; Divya Rishi Shrivastava; Rakesh Kumar Sharma (Fuel, 2023)

Biomethanol production from renewable resources: a sustainable approach - Sanjukta Subudhi; Koel Saha; Divya Mudgil; Prakash Kumar Sarangi; Rajesh K. Srivastava; Mrinal Kumar Sarma (Environmental Science and Pollution Research, 2023)

Impact of prepubertal bovine ovarian tissue pre-freeze holding duration on follicle quality - Divya Deeleep Bhagat Amonkar; Vincenzo Genovese; Vincenza De Gregorio; Angela Travaglione; Shubhashree Uppangala; R. Vani Lakshmi; Guruprasad Kalthur; Roberto Gualtieri; Riccardo Talevi; Satish Kumar Adiga (Reproductive Biology, 2023)

Interlaboratory study: Testing reproducibility of solid biofuels component identification using reflected light microscopy - Agnieszka Drobniak; Maria Mastalerz; Zbigniew Jelonek; Iwona Jelonek; Tushar Adsul; Neža Malenšek Andolšek; Omid Haeri Ardakani; Tara Congo; Batbold Demberelsuren; Bryon S. Donohoe; Ashley Douds; Deolinda Flores; et al. (International Journal of Coal Geology, 2023)

Effects of Different Concentration of Copper on Performance, Immunity and Carcass Traits in Broiler Japanese Quails - Chandra Deo; Avishek Biswas; Divya Sharma; Ashok Kumar Tiwari (Biological Trace Element Research, 2023)

Urban growth trend analysis of proposed Greater Silchar City, India, using landscape metrics and Shannon entropy model - Divya Prakash Mohabey; Jenita M. Nongkynrih; Upendra Kumar (Environment, Development and Sustainability, 2023)

Surface and thermocline ocean circulation intensity changes in the western Arabian Sea during ∼172 kyr - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Shailesh Agrawal; Pankaj Kumar; Brijesh Kumar; Divya Verma (Quaternary Science Reviews, 2023)

Role of RhoG as a regulator of cellular functions: integrating insights on immune cell activation, migration, and functions - Shubham Kumar Rai; Divya Singh; Pranita P. Sarangi (Inflammation Research, 2023)

The projected changes in extreme wave height indices over the Indian Ocean using COWCLIP2.0 datasets - Divya Sardana; Prashant Kumar; Prasad K. Bhaskaran; T. M. Balakrishnan Nair (Climate Dynamics, 2023)

Soil and Ocean Carbon Sequestration, Carbon Capture, Utilization, and Storage as Negative Emission Strategies for Global Climate Change - Divya Pant; Kabita Kumari Shah; Sadikshya Sharma; Maya Bhatta; Subina Tripathi; Hari Prasad Pandey; Himanshu Tiwari; Jiban Shrestha; Ashbin Kumar Bhat (Journal of Soil Science and Plant Nutrition, 2023)

Genome-wide identification and expression analysis of the Pisum sativum (L.) APETALA2/ethylene-responsive factor (AP2/ERF) gene family reveals functions in drought and cold stresses - Trishna Jarambasa; Preetom Regon; Sabnoor Yeasrin Jyoti; Divya Gupta; Sanjib Kumar Panda; Bhaben Tanti (Genetica, 2023)

Comparative transcriptome profiling of near isogenic lines PBW343 and FLW29 to unravel defense related genes and pathways contributing to stripe rust resistance in wheat - Zahoor Ahmad Mir; Divya Chauhan; Anjan Kumar Pradhan; Vivek Srivastava; Divya Sharma; Neeraj Budhlakoti; Dwijesh Chandra Mishra; Vasudha Jadon; Tanmaya Kumar Sahu; Monendra Grover; Om Prakash Gangwar; Subodh Kumar; et al. (Functional & Integrative Genomics, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

N-Glycoprofiling of immunoglobulin G and lactoperoxidase from sheep milk using LC-MS/MS - M. Sudarshan; V. Divya Shree; P. Jyothibai; B.S. Gnanesh Kumar (International Dairy Journal, 2023)

A propitious role of marine sourced polysaccharides: Drug delivery and biomedical applications - Ameya Sharma; Ishnoor Kaur; Divya Dheer; Manju Nagpal; Pradeep Kumar; D. Nagasamy Venkatesh; Vivek Puri; Inderbir Singh (Carbohydrate Polymers, 2023)

Bioengineering of biowaste to recover bioproducts and bioenergy: A circular economy approach towards sustainable zero-waste environment - Vinay Kumar; Alisa S. Vangnai; Neha Sharma; Komalpreet Kaur; Pritha Chakraborty; Mridul Umesh; Barkha Singhal; Divya Utreja; Edgar Uquiche Carrasco; Rodrigo Andler; Mukesh Kumar Awasthi; Mohammad J. Taherzadeh (Chemosphere, 2023)

Novel Biocompatible Green Silver Nanoparticles Efficiently Eliminates Multidrug Resistant Nosocomial Pathogens and Mycobacterium Species - Shahbaz Aman; Narinder Kaur; Divya Mittal; Deepanjali Sharma; Komal Shukla; Bharat Singh; Anchita Sharma; Samarjeet Singh Siwal; Vijay Kumar Thakur; Hemant Joshi; Raju Gupta; Reena V. Saini; et al. (Indian Journal of Microbiology, 2023)

Gamma radiation dose rate distribution in the Anand, Bharuch, Vadodara, and Narmada districts of Gujarat, India - Divya Patel; Manoj Kumar Jindal; Padmaja Sudhakar Pamidimukkala; Debjani Chakraborty (Environmental Science and Pollution Research, 2023)

RBM47 is a Critical Regulator of Mouse Embryonic Stem Cell Differentiation - Pavan Kumar Mysuru Shivalingappa; Divya Kumari Singh; Vaishali Sharma; Vivek Arora; Anjali Shiras; Sharmila A. Bapat (Stem Cell Reviews and Reports, 2023)

Influence of climate variability on sea level rise and its teleconnection with sea surface temperature anomalies over the Indo‐Pacific Ocean - Prashant Kumar; Divya Sardana; Evan Weller; Prasad K. Bhaskaran (International Journal of Climatology, 2022)
Rising sea levels pose a potential threat to the low‐lying regions for the countries that surround the Indo‐Pacific belt. Changes in sea level and its variability are intrinsically connected with sea surface temperature (SST) variations and associated wind field patterns in the Indo‐Pacific Ocean (IPO). SST‐based climate variability modes such as El Niño–Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), and Pacific Decadal Oscillation (PDO) tend to influence the sea level variability over the IPO significantly. The impact of climate variability modes on SLA, SST, and wind speed is examined by using regression analysis. The study considered two different datasets, namely the AVISO SLA and reconstructed SSHA from 1993 to 2019 and 1952 to 2009, respectively. SLA and SST both exhibit a decreasing trend from 1997 to 2007 year‐round; however, by the next decade (2008–2018), an overall increasing trend is evident in both parameters throughout the year. The influence of independent ENSO after removing the PDO signal (ENSO| PDO ) on SLA and SST exhibits statistically significant increases over the eastern PO, western tropical IO, but decreases over the AS, eastern IO, and western PO during DJF. SLA response to IOD removing ENSO (IOD| ENSO ) during SON includes increases over western to central tropical IO, and decreases over the AS extending up to eastern IO. Lastly, for the PDO influence in DJF, statistically significant increases in SLA are evident over the north PO extending up to eastern PO; however, PDO| ENSO influence over SLA exhibits similar but significantly reduced amplitudes. Composite analysis of different phase combinations of PDO (IOD) with El Niño (La Niña) exhibits stronger (weaker) influences during DJF (SON) season.

Outbreak and Management of Serpentine Leaf Miner, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae), on Potato (Solanum tuberosum L.) Crop in India - Priyank Hanuman Mhatre; Shivaji Hausrao Thube; Om Navik; E. P. Venkatasalam; Sanjeev Sharma; Jagadeesh Patil; S. Subhash; K. L. Divya; Santosh Watpade; Thava Prakash Pandian; M. Abas Shah; Manoj Kumar (Potato Research, 2022)

Genome-wide identification and characterization of glutathione S-transferase gene family in Musa acuminata L. AAA group and gaining an insight to their role in banana fruit development - Swati Vaish; Reshma Parveen; Divya Gupta; Mahesh Kumar Basantani (Journal of Applied Genetics, 2022)

Integration of Constructed Wetland Microcosms with Available Wastewater Treatment Technologies for the Polishing of Domestic Wastewater and Their Potential Reuses - Saroj Kumar; Bhanu Pratap; Divya Dubey; Venkatesh Dutta (International Journal of Environmental Research, 2022)

Constructed wetlands for the removal of pharmaceuticals and personal care products (PPCPs) from wastewater: origin, impacts, treatment methods, and SWOT analysis - Saroj Kumar; Bhanu Pratap; Divya Dubey; Adarsh Kumar; Saurabh Shukla; Venkatesh Dutta (Environmental Monitoring and Assessment, 2022)

Three territory sign in COVID-19 - Prashant Bhatele; Animesh Das; Awadh Kishor Pandit; Divya M. Radhakrishnan; Achal Kumar Srivastava (Acta Neurologica Belgica, 2022)

MOG antibody-positive paraneoplastic myelopathy in breast carcinoma: the new culprit - Ajith Cherian; Sharath Chandra Shetty; K. P. Divya; Pranab Karipody Prabhakaran; Harini Pavuluri; Naveen Kumar Paramasivan (Acta Neurologica Belgica, 2022)

Understanding precipitation characteristics of Afghanistan at provincial scale - Shakti Suryavanshi; Nitin Joshi; Hardeep Kumar Maurya; Divya Gupta; Keshav Kumar Sharma (Theoretical and Applied Climatology, 2022)

Computational insights into diverse aspects of glutathione S-transferase gene family in Papaver somniferum - Swati Vaish; Reshma Parveen; Rajneesh; Nootan Singh; Divya Gupta; Mahesh Kumar Basantani (Journal of Plant Research, 2022)

Activated Hollow and Solid Carbon Spheres for Enhanced Removal Efficiency of Pharmaceutical Pollutants and Heavy Metals in Water - Devika Laishram; Divya Kumar; Vishav Kant; Bhagirath Saini; Kiran P. Shejale; R. Krishnapriya; Vikash C. Janu; Rahul Singhal; Rakesh K. Sharma (Water, Air, & Soil Pollution, 2022)

Influence of climate variability on wind‐sea and swell wave height extreme over the Indo‐Pacific Ocean - Prashant Kumar; Divya Sardana; Sukhwinder Kaur; Remya PG; Rajni; Evan Weller (International Journal of Climatology, 2022)
In the Indo‐Pacific Ocean (IPO), extreme significant wave heights (SWHs) can substantially induce coastal erosion, flooding, and devastating impacts on coastal livelihoods. This study examines the seasonal influence of the El Niño–Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), Southern Annular Mode (SAM), and Pacific North American (PNA) pattern on extreme wind‐wave parameters. The climatic extremes are calculated utilizing ERA5 reanalysis datasets from 1979 to 2019 and a nonstationary generalized extreme value distribution. Significant increases in extreme wind‐sea (Hmax) and swell SWH (Hmax Sw ) response to ENSO occur over the northeast North Pacific (NP) during December–February (DJF) and western NP during June–August (JJA). The PNA influence exhibits a similar pattern to ENSO during DJF yet is inactive in JJA. Hmax and Hmax Sw responses to the IOD during September–November (SON) include significant increases over the western Pacific, southern Indian Ocean (IO), and southwest tropical IO, yet decreases over the central tropical IO. The Hmax Sw response to the SAM is larger than that for Hmax over the southern IPO during DJF, which extends toward the eastern Pacific in March–May (MAM). Overall, extreme wind‐sea and swell parameter responses are found to be associated with sea level pressure (SLP) and SLP gradients.

Interference of bio-control Trichoderma to enhance physical and physiological strength of sugarcane during Pokkah boeng infection - Raghvendra Tiwari; Kajal Chandra; S. K. Shukla; V. P. Jaiswal; Natarajan Amaresan; Abhay Kumar Srivastava; Asha Gaur; Divya Sahni; Rajesh Kumar Tiwari (World Journal of Microbiology and Biotechnology, 2022)

Serum glucose-regulated protein 78 (GRP78) levels in COVID-19-associated mucormycosis: results of a case–control study - Valliappan Muthu; Manpreet Dhaliwal; Arunima Sharma; Divya Nair; H. Mohan Kumar; Shivaprakash M. Rudramurthy; Inderpaul Singh Sehgal; Hansraj Choudhary; Naresh Panda; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2022)

Energy and environmental analysis of a solar evacuated tube heat pipe integrated thermoelectric generator using IoT - Sakthi Priya Manivannan; Divya Laxmi Gunasekaran; Gowthami Jaganathan; Shanthi Natesan; Sabari Muthu Muthusamy; Sung Chul Kim; Balaji Kumar; Ganesh Kumar Poongavanam; Sakthivadivel Duraisamy (Environmental Science and Pollution Research, 2022)

Seasonal extreme rainfall variability over India and its association with surface air temperature - Divya Sardana; Prashant Kumar; Evan Weller; Rajni (Theoretical and Applied Climatology, 2022)

Improved machine learning scoring functions for identification of Electrophorus electricus’s acetylcholinesterase inhibitors - Ankit Ganeshpurkar; Ravi Singh; Shalini Shivhare; Divya; Devendra Kumar; Gopichand Gutti; Ravibhushan Singh; Ashok Kumar; Sushil Kumar Singh (Molecular Diversity, 2022)

p-Menthadienols-rich essential oil from Cymbopogon martini ameliorates skin inflammation - Swati Singh; Divya Bhatt; Munmun Kumar Singh; Anil Kumar Maurya; KM Monazza Israr; Amit Chauhan; Rajendra Chandra Padalia; Ram Swaroop Verma; Dnyaneshwar U. Bawankule (Inflammopharmacology, 2022)

Utilization of agricultural waste biomass and recycling toward circular bioeconomy - Prakash Kumar Sarangi; Sanjukta Subudhi; Latika Bhatia; Koel Saha; Divya Mudgil; Krushna Prasad Shadangi; Rajesh K. Srivastava; Bhabjit Pattnaik; Raj Kumar Arya (Environmental Science and Pollution Research, 2022)

Endogenous phytonutrient, phytochemical, and phytohormone levels modulate in-vitro callus induction and plant regeneration in finger millet ( Eleusine coracana ) genotypes - Gautam Jamra; Pallavi Shah; Aparna Agarwal; Divya Sharma; Anil Kumar (Plant Biosystems, 2022)

The Origin and Clinical Relevance of Yoga Nidra - Seithikurippu R. Pandi-Perumal; David Warren Spence; Neena Srivastava; Divya Kanchibhotla; Kamakhya Kumar; Gaurav Saurabh Sharma; Ravi Gupta; Gitanjali Batmanabane (Sleep and Vigilance, 2022)

Mesenchymal Stem Cell Therapy in the Treatment of Neurodegenerative Cerebellar Ataxias: a Systematic Review and Meta-analysis - Manish Bhartiya; Amit Kumar; Rakesh K. Singh; Divya M Radhakrishnan; Roopa Rajan; Achal Kumar Srivastava (The Cerebellum, 2022)

Unraveling genetic admixture in the Indian crossbred cattle by different approaches using Bovine 50K BeadChip - Dhan Pal; Manjit Panigrahi; Supriya Chhotaray; Harshit Kumar; Sonali Sonejita Nayak; Divya Rajawat; Subhashree Parida; G. K. Gaur; Triveni Dutt; Bharat Bhushan (Tropical Animal Health and Production, 2022)

Weight–length Relationships and Fulton’s Condition Factors of Ten Commercially Important Scombridae Fish Species in Southeast Coast of India, Bay of Bengal - Kannan Karuppiah; Kannapiran Ethiraj; Sivaranjani Sekar; Kumar Rajendran; Madhuri Krishnamoorthy; Divya Dharmaraj (Thalassas: An International Journal of Marine Sciences, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Direct Molecular Detection of Drug-Resistant Tuberculosis from Transported Bio-Safe Dried Sputum on Filter-Paper - Divya Anthwal; Shaina Jamwal; Rakesh Kumar Gupta; Ritu Singhal; Ajoy Kumar Verma; Manpreet Bhalla; Vithal Prasad Myneedu; Rohit Sarin; Sangeeta Choudhary; Jaya Sivaswami Tyagi; Sagarika Haldar (Current Microbiology, 2022)

Anti-ulcerogenic potential of anthocyanin-loaded chitosan nanoparticles against alcohol-HCl induced gastric ulcer in rats - Sreerekha Perumcherry Raman; Pavan Kumar Dara; Divya K Vijayan; Niladri Sekhar Chatterjee; Mahadevan Raghavankutty; Suseela Mathew; Chandragiri Nagarajarao Ravishankar; Rangasamy Anandan (Natural Product Research, 2022)

Rutin ameliorates malaria pathogenesis by modulating inflammatory mechanism: an in vitro and in vivo study - Divya Bhatt; Saurabh Kumar; Parmanand Kumar; Surbhi Bisht; Anant Kumar; Anil Kumar Maurya; Anirban Pal; Dnyaneshwar Umrao Bawankule (Inflammopharmacology, 2022)

Benzofuran pyran hybrid prevents glucocorticoid induced osteoporosis in mice via modulation of canonical Wnt/β-catenin signaling - Ashish Kumar Tripathi; Divya Rai; Priyanka Kothari; Pragati Kushwaha; Koneni V. Sashidhara; Ritu Trivedi (Apoptosis, 2022)

Pyrrolo[2,1-f][1,2,4]triazine: a promising fused heterocycle to target kinases in cancer therapy - Sarbjit Singh; Divya Utreja; Vimal Kumar (Medicinal Chemistry Research, 2022)

Biomedical applications of electrospun nanofibers in the management of diabetic wounds - Divya Pamu; Vyshnavi Tallapaneni; Veera Venkata Satyanarayana Reddy Karri; Sachin Kumar Singh (Drug Delivery and Translational Research, 2022)

A comprehensive study on preparedness, impacts, response and recovery from tropical severe cyclonic storm ‘GAJA’: lessons for the future - S. Leo George; K. Balasubramani; Sulochana Shekhar; E. Venkatesham; K. Arun Prasad; Aakriti Grover; Dinabandhu Mahata; Ashish Kumar; V. V. Ashique; R. S. Libina; Divya Rajeswari Swaminathan; A. Balasundareshwaran; et al. (Journal of Coastal Conservation, 2021)

Myelopathy due to fibrocartilaginous embolism: elephant in the room - K. P. Divya; Ajith Cherian; Naveen Kumar Paramasivan; Jaffar Vali Sayyed (Acta Neurologica Belgica, 2021)

Isolated cortical lingual palsy: a slip of the tongue - Jaffar Vali Sayyed; K. P. Divya; Ajith Cherian; Naveen Kumar Paramasivan; S. Krishna (Acta Neurologica Belgica, 2021)

Purification and characterization of Cyclophilin: a protein associated with protein folding in Salmonella Typhimurium - Manoj Kumawat; Divya Chaudhary; Bilkees Nabi; Manoj Kumar; Devojit Kumar Sarma; Swasti Shubham; Irungbam Karuna; Neeraj Ahlawat; Sushma Ahlawat (Archives of Microbiology, 2021)

Acellular Scaffolds as Innovative Biomaterial Platforms for the Management of Diabetic Wounds - Vyshnavi Tallapaneni; C. Kalaivani; Divya Pamu; Lavanya Mude; Sachin Kumar Singh; Veera Venkata Satyanarayana Reddy Karri (Tissue Engineering and Regenerative Medicine, 2021)

Re-Description of Sillago malabarica, Silver Whiting from Southern Indian Waters - P. R. Divya; Rahul G. Kumar; Linu Joy; C. P. Rajool Shanis; V. S. Basheer; K. K. Lal (Thalassas: An International Journal of Marine Sciences, 2021)

Improvement of small seed for big nutritional feed - P. B. Kavi Kishor; S. Anil Kumar; Jalaja Naravula; P. Hima Kumari; Divya Kummari; Rajasheker Guddimalli; Sujatha Edupuganti; Appa Rao Karumanchi; Perumal Venkatachalam; Prashanth Suravajhala; Rathnagiri Polavarapu (Physiology and Molecular Biology of Plants, 2021)

Single gene variants causing deafness in Asian Indians - Inusha Panigrahi; Divya Kumari; B. N. Anil Kumar (Journal of Genetics, 2021)

Optimising drip irrigation and fertigation schedules for higher crop and water productivity of oilseed rape (Brassica napus L.) - Divya S. Kumar; Rajni Sharma; A. S. Brar (Irrigation Science, 2021)

Recent advances in satellite mapping of global air quality: evidences during COVID-19 pandemic - Venkatesh Dutta; Saroj Kumar; Divya Dubey (Environmental Sustainability, 2021)

Genetic analysis of colorectal carcinoma using high throughput single nucleotide polymorphism genotyping technique within the population of Jammu and Kashmir - Bhanu Sharma; Shabab Angurana; Amrita Bhat; Sonali Verma; Divya Bakshi; Ghulam Rasool Bhat; Rajeshwer Singh Jamwal; Asif Amin; Raies Ahmed Qadri; Ruchi Shah; Rakesh Kumar (Molecular Biology Reports, 2021)

Strategic Supplementation of Antioxidant Micronutrients in Peri-parturient Murrah Buffaloes Helps Augment the Udder Health and Milk Production - Himanshu Pratap Singh; Ravindra Kumar Jain; Divya Tiwari; Mukesh Kumar Mehta; Vishal Mudgal (Biological Trace Element Research, 2021)

Dopa-responsive dystonia, DRD-plus and DRD look-alike: a pragmatic review - Ajith Cherian; Naveen Kumar Paramasivan; K. P. Divya (Acta Neurologica Belgica, 2021)

Beneficial microbiomes for bioremediation of diverse contaminated environments for environmental sustainability: present status and future challenges - Divjot Kour; Tanvir Kaur; Rubee Devi; Ashok Yadav; Manali Singh; Divya Joshi; Jyoti Singh; Deep Chandra Suyal; Ajay Kumar; Vishnu D. Rajput; Ajar Nath Yadav; Karan Singh; et al. (Environmental Science and Pollution Research, 2021)

Effect of PDGF-B Gene-Activated Acellular Matrix and Mesenchymal Stem Cell Transplantation on Full Thickness Skin Burn Wound in Rat Model - Tamilmahan Paramasivam; Swapan Kumar Maiti; Sangeetha Palakkara; Rashmi; Divya Mohan; H. V. Manjunthaachar; K. Karthik; Naveen Kumar (Tissue Engineering and Regenerative Medicine, 2021)

Occurrence and removal of antibiotics from industrial wastewater - D. Akhil; Divya Lakshmi; P. Senthil Kumar; Dai-Viet N. Vo; A. Kartik (Environmental Chemistry Letters, 2021)

Exploration of Heat Stress-Responsive Markers in Understanding Trait Associations in Wheat - P. B. Manjunatha; Nivedita Sinha; Hari Krishna; Divya Chauhan; Pawan Kumar; Ranjeet R. Kumar; Neelu Jain; P. K. Singh; G. P. Singh (Journal of Plant Biology, 2021)

Experimental Evaluation of Seaweeds Liquid Extracts as an Alternative Culture Medium on the Growth and Proximate Composition of Picochlorum maculatum - S. Bharathi; S. Dinesh Kumar; S. Sekar; P. Santhanam; M. Divya; N. Krishnaveni; M. Pragnya; B. Dhanalakshmi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Protective and therapeutic effects of sildenafil and tadalafil on aflatoxin B1-induced hepatocellular carcinoma - Saurabh K. Chhonker; Divya Rawat; Raj Kumar Koiri (Molecular and Cellular Biochemistry, 2021)

Obstructive Sleep Apnea Comorbid with Late-Onset Kleine–Levin Syndrome: A Rare Condition - M. P. Divya; Akash Kumar; Shivam Gupta; Sudheer Tale; Lokesh Kumar Saini; Ravi Gupta (Sleep and Vigilance, 2020)

Microsatellite marker development in Spanish mackerel Scomberomorus commerson using third generation sequencing technology - Linu Joy; Sunitha Paulose; PR Divya; Charan Ravi; VS Basheer; Rajesh Kumar; Rajeev Kumar Singh; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2020)

RECK and TIMP-2 mediate inhibition of MMP-2 and MMP-9 by Annona muricata - G Drishya; Jyotsna Nambiar; Sanu K Shaji; Muralidharan Vanuopadath; A Achuthan; Abishek Kumar; Ashna Alias; Ayesha Sherif; Catherine Joseph; P Divya; Damu Sunil Kumar; Chinchu Bose; et al. (Journal of Biosciences, 2020)

Removal of nutrients from domestic wastewater using constructed wetlands: assessment of suitable environmental and operational conditions - Saroj Kumar; Bhanu Pratap; Divya Dubey; Venkatesh Dutta (Environmental Sustainability, 2020)

Alliance between selective serotonin reuptake inhibitors and fracture risk: an updated systematic review and meta-analysis - Manoj Kumar; Ram Bajpai; Abdul Rahaman Shaik; Swati Srivastava; Divya Vohora (European Journal of Clinical Pharmacology, 2020)

Metaproteomic insights into ammonia oxidising bacterial consortium developed for bioaugmenting nitrification in aquaculture systems - Divya Jose; Prasannan Geetha Preena; Vattiringal Jayadradhan Rejish Kumar; Rosamma Philip; Isaac Sarojini Bright Singh (Biologia, 2020)

Purification and biochemical characterization of a novel secretory dipeptidyl peptidase IV from porcine serum - Divya Kumar; Vivek K. Hamse; K. N. Neema; Priya Babu Shubha; D. M. Chetan; Nanjunda Swamy Shivananju (Molecular and Cellular Biochemistry, 2020)

Rejection of the beneficial acclimation hypothesis (BAH) for short term heat acclimation in Drosophila nepalensis - Seema Ramniwas; Girish Kumar; Divya Singh (Genetica, 2020)

Population connectivity and genetic structure of Asian green mussel, Perna viridis along Indian waters assessed using mitochondrial markers - P. R. Divya; P. M. Elizabeth Jency; Linu Joy; A. Kathirvelpandian; Rajeev Kumar Singh; V. S. Basheer (Molecular Biology Reports, 2020)

Evaluation of genetic diversity of parental lines for development of heterotic groups in hybrid rice (Oryza sativa L.) - K. Sruthi; B. Divya; P. Senguttuvel; P. Revathi; K. B. Kemparaju; P. Koteswararao; R. M. Sundaram; Vikram Jeet Singh; E. Ranjith Kumar; Prolay Kumar Bhowmick; K. K. Vinod; S. Gopala Krishnan; et al. (Journal of Plant Biochemistry and Biotechnology, 2020)

Spatial variations of heavy metal contamination and associated risks around an unplanned landfill site in India - Parul Johar; Divya Singh; Arun Kumar (Environmental Monitoring and Assessment, 2020)

Molecular fossils “pseudogenes” as functional signature in biological system - Rajesh Kumar Singh; Divya Singh; Arpana Yadava; Akhileshwar Kumar Srivastava (Genes & Genomics, 2020)

A Review on Bioactive Peptides: Physiological Functions, Bioavailability and Safety - Divya Bhandari; Shafiya Rafiq; Yogesh Gat; Punam Gat; Roji Waghmare; Vikas Kumar (International Journal of Peptide Research and Therapeutics, 2020)

Genetics of novel brown planthopper Nilaparvata lugens (Stål) resistance genes in derived introgression lines from the interspecific cross O. sativa var. Swarna × O. nivara - S. Akanksha; V. Jhansi Lakshmi; Arun Kumar Singh; Yamini Deepthi; P. M. Chirutkar; Ramdeen; Divya Balakrishnan; N. Sarla; S. K. Mangrauthia; T. Ram (Journal of Genetics, 2019)

Bioimaging Applications of Carbon dots (C. dots) and its Cystamine Functionalization for the Sensitive Detection of Cr(VI) in Aqueous Samples - Roshni V.; Varsha Gujar; Heena Pathan; Sehbanul Islam; Madhumita Tawre; Karishma Pardesi; Manas Kumar Santra; Divya Ottoor (Journal of Fluorescence, 2019)

Assessment of toxic interaction of nano zinc oxide and nano copper oxide on germination of Raphanus sativus seeds - Divya Singh; Arun Kumar (Environmental Monitoring and Assessment, 2019)

Comparative overview of red kidney bean (Phaseolus valgaris) rhizospheric bacterial diversity in perspective of altitudinal variations - Deep Chandra Suyal; Saurabh Kumar; Divya Joshi; Amit Yadav; Yogesh Shouche; Reeta Goel (Biologia, 2019)

Antimicrobial therapeutics delivery systems based on biodegradable polylactide/polylactide-co-glycolide particles - Robin Kumar; Divya Jha; Amulya K. Panda (Environmental Chemistry Letters, 2019)

Tenecteplase versus alteplase in acute ischemic stroke: systematic review and meta-analysis - A. Thelengana; Divya M. Radhakrishnan; Manya Prasad; Amit Kumar; Kameshwar Prasad (Acta Neurologica Belgica, 2019)

Seasonal variations in culturable archaea and their plant growth promoting attributes to predict their role in establishment of vegetation in Rann of Kutch - Ajar Nath Yadav; Sneha Gulati; Divya Sharma; Ram Nageena Singh; Mahendra Vikram Singh Rajawat; Rajesh Kumar; Rinku Dey; Kamal Krishna Pal; Rajeev Kaushik; Anil Kumar Saxena (Biologia, 2019)

Genetic population structure of a highly migratory Hilsa Shad, Tenualosa ilisha, in three river systems, inferred from four mitochondrial genes analysis - Vindhya Mohindra; B. K. Divya; Rajesh Kumar; Rajeev K. Singh; Arvind Kumar Dwivedi; Sangeeta Mandal; Prachi Masih; Kuldeep K. Lal; J. K. Jena (Environmental Biology of Fishes, 2019)

In silico prediction of short hairpin RNA and in vitro silencing of activin receptor type IIB in chicken embryo fibroblasts by RNA interference - P. Guru Vishnu; T. K. Bhattacharya; Bharat Bhushan; Pushpendra Kumar; R. N. Chatterjee; Chandan Paswan; K. Dushyanth; D. Divya; A. Rajendra Prasad (Molecular Biology Reports, 2019)

Genetic variant rs10937405 of TP63 and susceptibility to lung cancer risk in north Indian population - GH. Rasool Bhat; Amrita Bhat; Sonali Verma; Itty Sethi; Ruchi Shah; Varun Sharma; S. Minerva; Divya Bakshi; Bhanu Sharma; Sandeep Koul; Deepak Abrol; Audesh Bhat; et al. (Journal of Genetics, 2019)

Cocrystal of 5-Fluorouracil: Characterization and Evaluation of Biopharmaceutical Parameters - Manoj Kumar Gautam; Mousumi Besan; Divya Pandit; Sanjay Mandal; Renu Chadha (AAPS PharmSciTech, 2019)

Evaluation of Potential Human Health Risks from Toxic Metals via Consumption of Cultured Fish Species Labeo rohita: A Case Study from an Urban Aquaculture Pond - Divya Pal; Subodh Kumar Maiti (Exposure and Health, 2019)

Heavy metal speciation, leaching and toxicity status of a tropical rain-fed river Damodar, India - Divya Pal; Subodh Kumar Maiti (Environmental Geochemistry and Health, 2018)

Application of Hidden Markov Model for avalanche danger simulations for road sectors in North-West Himalaya - Jagdish Chandra Joshi; Tankeshwar Kumar; Sunita Srivastava; Divya Sachdeva; Ashwagosha Ganju (Natural Hazards, 2018)

Mesenchymal Stem Cells of Different Origin-Seeded Bioceramic Construct in Regeneration of Bone Defect in Rabbit - Swapan Kumar Maiti; M. U. Shivakumar; Divya Mohan; Naveen Kumar; Karam Pal Singh (Tissue Engineering and Regenerative Medicine, 2018)

Molecular characterization and expression profiling of BMP 3 gene in broiler and layer chicken - Devara Divya; Tarun Kumar Bhattacharya; Manthani Gnana Prakash; R. N. Chatterjee; Renu Shukla; Pothana Boyina Guru Vishnu; Amirthalingam Vinoth; Kotha Dushyanth (Molecular Biology Reports, 2018)

In vitro efficacy of amitraz, coumaphos, deltamethrin and lindane against engorged female Rhipicephalus (Boophilus) annulatus and Haemaphysalis bispinosa ticks - Reghu Ravindran; Gopi Jyothimol; Krishnan Kavillimakkil Amithamol; Athalathil Ramankutty Sunil; Leena Chandrasekhar; Dibya Ranjan Lenka; Achuthkumar Amritha; Kanapadinchareveetil Sreelekha; Nanjundappa Sathish; Darsana Udayan; Thumadath Palayullaparambil Adarsh Krishna; Thirumangalath Meethal Divya; et al. (Experimental and Applied Acarology, 2018)

Seasonal variation of heavy metals in water, sediment, and highly consumed cultured fish (Labeo rohita and Labeo bata) and potential health risk assessment in aquaculture pond of the coal city, Dhanbad (India) - Divya Pal; Subodh Kumar Maiti (Environmental Science and Pollution Research, 2018)

Identifying Challenges in Assessing Risks of Exposures of Silver Nanoparticles - Jyoti Chawla; Divya Singh; Baranidharan Sundaram; Arun Kumar (Exposure and Health, 2018)

MicroRNA in gastrointestinal cell signalling - Priyanka Mishra; Divya Singh; Lilly Ganju; Bhuvnesh Kumar (Inflammopharmacology, 2018)

Dimethylarginine dimethylaminohydrolase-1 (DDAH1) is frequently upregulated in prostate cancer, and its overexpression conveys tumor growth and angiogenesis by metabolizing asymmetric dimethylarginine (ADMA) - Karthik Reddy Kami Reddy; Chandrashekhar Dasari; Divya Duscharla; Bhukya Supriya; N. Sai Ram; M. V. Surekha; Jerald Mahesh Kumar; Ramesh Ummanni (Angiogenesis, 2018)

Assessing biodegradation of furfuryl alcohol using Pseudomonas putida MTCC 1194 and Pseudomonas aeruginosa MTCC 1034 and its kinetics - Rakesh Kumar; Divya Rashmi (World Journal of Microbiology and Biotechnology, 2018)

Investigating long-term effect of nanoparticles on growth of Raphanus sativus plants: a trans-generational study - Divya Singh; Arun Kumar (Ecotoxicology, 2018)

Molecular and in Silico Characterization of Achaea janata Granulovirus Granulin Gene - Pola Naveen Kumar; Yenumula Gerard Prasad; Mathyam Prabhakar; Arun K. Shanker; Divya Bhanu (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Pancreatic Cancer: Current Status and Challenges - Amanda R. Muñoz; Divya Chakravarthy; Jingjing Gong; Glenn A. Halff; Rita Ghosh; Addanki P. Kumar (Current Pharmacology Reports, 2017)

Synthesis, antioxidant, and antiviral properties of pyrimidinylsulfamoyl azolyl acetamides - Kuppi Reddy Gari Divya; Donthamsetty V. Sowmya; Suram Durgamma; Vadlamudi Tharanath; Divi Venkataramana Sai Gopal; Malaka Venkateshwarulu Jyothi Kumar; Chippada Appa Rao; Adivireddy Padmaja; Venkatapuram Padmavathi (Medicinal Chemistry Research, 2017)

Novel combination of salinomycin and resveratrol synergistically enhances the anti-proliferative and pro-apoptotic effects on human breast cancer cells - Jayant Dewangan; Divya Tandon; Sonal Srivastava; Ajeet Kumar Verma; Ashok Yapuri; Srikanta Kumar Rath (Apoptosis, 2017)

Correlation of edge truncation with antibacterial activity of plate-like anisotropic silver nanoparticles - Divya Goyal; Gaganpreet Kaur; Rupinder Tewari; Rajesh Kumar (Environmental Science and Pollution Research, 2017)

Comparative assessment of some physiological and cytological attributes following gamma irradiation exposure to dry and dry irradiated stored seeds of Nigella sativa L. (black cumin) - Divya Vishambhar Kumbhakar; Animesh Kumar Datta; Debadrito Das; Bapi Ghosh; Ankita Pramanik (The Nucleus, 2017)

Enhancement of the Oral Bioavailability of Felodipine Employing 8-Arm-Poly(Ethylene Glycol): In Vivo, In Vitro and In Silico Evaluation - Pius Fasinu; Yahya E. Choonara; Pradeep Kumar; Lisa C. du Toit; Divya Bijukumar; Riaz A. Khan; Viness Pillay (AAPS PharmSciTech, 2017)

Structural Interactions of Curcumin Biotransformed Molecules with the N-Terminal Residues of Cytotoxic-Associated Gene A Protein Provide Insights into Suppression of Oncogenic Activities - Akhileshwar Kumar Srivastava; Divya Singh; Bijoy Krishna Roy (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Spatio-Temporal Monitoring and Ecological Significance of Retrievable Pelagic Heterotrophic Bacteria in Kongsfjorden, an Arctic Fjord - Rupesh Kumar Sinha; K. P. Krishnan; Savita Kerkar; T. Divya David (Indian Journal of Microbiology, 2017)

Optimisation of Hidden Markov Model using Baum–Welch algorithm for prediction of maximum and minimum temperature over Indian Himalaya - J C JOSHI; TANKESHWAR KUMAR; SUNITA SRIVASTAVA; DIVYA SACHDEVA (Journal of Earth System Science, 2017)

Population-level diversity in the association of genetic polymorphisms of one-carbon metabolism with breast cancer risk - Shaik Mohammad Naushad; Chandrasekhar Divya; M. Janaki Ramaiah; Tajamul Hussain; Salman A. Alrokayan; Vijay Kumar Kutala (Journal of Community Genetics, 2016)

Impact of Irrigation Using Water Containing CuO and ZnO Nanoparticles on Spinach oleracea Grown in Soil Media - Divya Singh; Arun Kumar (Bulletin of Environmental Contamination and Toxicology, 2016)

Modulation of digestive enzymes, GH, IGF-1 and IGF-2 genes in the teleost, Tilapia (Oreochromis mossambicus) by dietary curcumin - Sebastian J. Midhun; Damodaran Arun; Lincy Edatt; M. V. Sruthi; V. V. Thushara; Oommen V. Oommen; V. B. Sameer Kumar; Lekha Divya (Aquaculture International, 2016)

Design of an Inflammation-Sensitive Polyelectrolyte-Based Topical Drug Delivery System for Arthritis - Divya Bijukumar; Yahya E. Choonara; Karmani Murugan; Bibi Fatima Choonara; Pradeep Kumar; Lisa C. du Toit; Viness Pillay (AAPS PharmSciTech, 2016)

Spatial variation of temperature and indicative of the urban heat island in Chennai Metropolitan Area, India - Anushiya Jeganathan; Ramachandran Andimuthu; Ramachandran Prasannavenkatesh; Divya Subash Kumar (Theoretical and Applied Climatology, 2016)

Effects of Nano Silver Oxide and Silver Ions on Growth of Vigna radiata - Divya Singh; Arun Kumar (Bulletin of Environmental Contamination and Toxicology, 2015)

Biomarker System for Genetic Analysis of Stored Grain Pests Callosobruchus maculatus and Callosobruchus chinensis - Divya Pandey; Bharat Neekhra; Meeta Mishra; Smita Banerjee; Subodh Kumar Jain (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Ultraviolet and 5′Fluorodeoxyuridine Induced Random Mutagenesis in Chlorella vulgaris and Its Impact on Fatty Acid Profile: A New Insight on Lipid-Metabolizing Genes and Structural Characterization of Related Proteins - Josephine Anthony; Vijaya Raghavan Rangamaran; Dharani Gopal; Kumar T. Shivasankarasubbiah; Mary Leema J. Thilagam; Magesh Peter Dhassiah; Divya Shridhar M. Padinjattayil; VinithKumar N. Valsalan; Vijayakumaran Manambrakat; Sivakumar Dakshinamurthy; Sivaraman Thirunavukkarasu; Kirubagaran Ramalingam (Marine Biotechnology, 2015)

Regulation of Gβγi-Dependent PLC-β3 Activity in Smooth Muscle: Inhibitory Phosphorylation of PLC-β3 by PKA and PKG and Stimulatory Phosphorylation of Gαi-GTPase-Activating Protein RGS2 by PKG - Ancy D. Nalli; Divya P. Kumar; Othman Al-Shboul; Sunila Mahavadi; John F. Kuemmerle; John R. Grider; Karnam S. Murthy (Cell Biochemistry and Biophysics, 2014)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

Differential expression analysis of transcripts related to oil metabolism in maturing seeds of Jatropha curcas L. - Divya Chandran; H. M. Sankararamasubramanian; M. Ashok Kumar; Ajay Parida (Physiology and Molecular Biology of Plants, 2014)

Comparative study of toxic chlorophenolic compounds generated in various bleaching sequences of wheat straw pulp - Rachna Malhotra; Divya Prakash; Sudheer Kumar Shukla; Taesung Kim; Satish Kumar; N. J. Rao (Clean Technologies and Environmental Policy, 2013)

Quantum Dots (QDs) Based Fluorescent Sensor for the Selective Determination of Nimesulide - Divya Thomas; Laina Lonappan; Leena Rajith; Soumya T. Cyriac; Krishnapillai Girish Kumar (Journal of Fluorescence, 2013)

Design, synthesis, and preliminary in vitro and in vivo pharmacological evaluation of 4-{4-[2-(4-(2-substitutedquinoxalin-3-yl)piperazin-1-yl)ethyl]phenyl}thiazoles as atypical antipsychotic agents - Kondapalli Venkata Gowri Chandra Sekhar; Vajja Sambasiva Rao; Winnie Deuther-Conrad; Divya Sridhar; Hunsur Nagendra Nagesh; Vellas Sreedhar Kumar; Peter Brust; Muthyala Murali Krishna Kumar (Medicinal Chemistry Research, 2013)

Traditional uses of medicinal plants for dermatological healthcare management practices by the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Anant Gopal Singh; Divya Darshan Tewari (Genetic Resources and Crop Evolution, 2013)

Morin protects heart from beta-adrenergic-stimulated myocardial infarction: an electrocardiographic, biochemical, and histological study in rats - Bharath Kumar Pogula; Mari Kannan Maharajan; Divya Rekha Oddepalli; Lavanya Boini; Mounika Arella; Darlin Quine Sabarimuthu (Journal of Physiology and Biochemistry, 2012)

Documentation and determination of consensus about phytotherapeutic veterinary practices among the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Divya Darshan Tewari (Tropical Animal Health and Production, 2012)

A bentazone-resistant mutant of cyanobacterium, Synechococcus elongatus PCC7942 adapts different strategies to counteract on bromoxynil- and salt-mediated oxidative stress - Suvendra Nath Bagchi; Palash Kumar Das; Sonali Banerjee; Mona Saggu; Divya Bagchi (Physiology and Molecular Biology of Plants, 2012)

Molecular characterization of eight Indian Snakehead species (Pisces: Perciformes Channidae) using RAPD markers - Ajaz Ali Bhat; M. A. Haniffa; P. R. Divya; A. Gopalakrishnan; M. James Milton; Raj Kumar; Bilal Ahmad Paray (Molecular Biology Reports, 2012)

Hydrochemical and water quality assessment of groundwater in Doon Valley of Outer Himalaya, Uttarakhand, India - Divya Dudeja; Sukesh Kumar Bartarya; A. K. Biyani (Environmental Monitoring and Assessment, 2011)

Phenotypic and genotypic characterization of Shigella spp. with reference to its virulence genes and antibiogram analysis from river Narmada - Anjana Sharma; Susheel Kumar Singh; Divya Bajpai (Indian Journal of Microbiology, 2009)

NAD+-dependent DNA ligase (Rv3014c) from M. tuberculosis: Strategies for inhibitor design - Divya Dube; Vandna Kukshal; Sandeep Kumar Srivastava; Rama Pati Tripathi; Ravishankar Ramachandran (Medicinal Chemistry Research, 2008)

Variation in the Nature of Organic Acid Secretion and Mineral Phosphate Solubilization by Citrobacter sp. DHRSS in the Presence of Different Sugars - Divya K. Patel; G. Archana; G. Naresh Kumar (Current Microbiology, 2008)

Composition of the essential oil from the root of Artemisia annua - Divya Goel; Richa Goel; Vijender Singh; Mohammed Ali; Gopal Rao Mallavarapu; Sushil Kumar (Journal of Natural Medicines, 2007)

Essential oils of petal, leaf and stem of the antimalarial plant Artemisia annua - Divya Goel; Vijender Singh; Mohammed Ali; Gopal Rao Mallavarupu; Sushil Kumar (Journal of Natural Medicines, 2007)